Compare the Clinical Application of Ureteroscopic Occluder and Stone Retrieval Basket During Holmium Laser Treatment for Upper Ureteral Calculi - Zhang, Lin; Wu, Yanyuan; Xu, Ke; Tang, Haixiao; Ding, Jie; Wang, Weimin; Xu, Ding; Gu, Zhengqin (Urology Journal, 2020)
Purpose: To explore the clinical efficacy of ureteroscopic occluder and stone retrieval basket combined with holmium laser in the treatment of upper ureteral calculi. Materials and Methods: This retrospective study included 103 patients treated with ureteroscopic holmium laser lithotripsy for upper ureteral stones. Patients were divided into two groups based on the device applied during lithotripsy: group 1 for the occluders (52 cases), and group 2 for the stone retrieval baskets (51 cases). The stone upward migration rate, stone-free rate, and complication rate during or after surgery were compared. Results: The operation time was 45 ± 7 min in the occluder group and 43 ± 5 min in the basket group (P = .111). There was no significant difference between the stone retropulsion rate (13% vs. 16%, P = .787). The successful one-time stone-free rate was 92% vs. 94% (P = .999) respectively. Furthermore, there was no significant difference in the hospitalization time (P = .581) and postoperative complication rate (P = .715) between 2 groups. Conclusion: The treatment of upper ureteral calculi with ureteroscopic occluder and stone retrieval basket combined with holmium laser lithotripsy can both effectively prevent intraoperative stone retropulsion, improve the success rate of one-time lithotrips. The occluder was more cost-effective than the stone retrieval basket, yet it was a more desired choice for over dilated ureters.